Intersecting Dimensions: Qualitative Investigation Into Financial Performance, Firm Valuation, Tax Compliance, Corporate Governance, And Leadership Dynamics - Salsabila Andrina; Ranti Karlaili (Pusat Riset dan Inovasi Nasional, 2022)
This research aims to explore the intricate interplay among financial performance, firm valuation, tax compliance, corporate governance, and leadership dynamics within organizations. The study employs a multi-dimensional model to investigate these interconnected aspects comprehensively. Sampling techniques involve purposive sampling to ensure representation across industries and organizational sizes. Data analysis utilizes thematic analysis to identify patterns, relationships, and emergent themes from qualitative data sources. Preliminary findings reveal complex interactions among the studied dimensions, highlighting the nuanced influence of leadership strategies, governance frameworks, and compliance practices on financial outcomes and firm valuation. The research contributes to a deeper understanding of the holistic dynamics shaping organizational performance and offers insights for practitioners and policymakers to enhance strategic decision-making and governance practices.